La representación discursiva de la identidad racial en las redes sociales - Sepúlveda Legorreta, Norma Patricia; Flores Treviño, María Eugenia (Comparative Cultural Studies: European and Latin American Perspectives, 2016)
The aim of this chapter is a brief review mainly of Hispanic and American theoretical contributions to address the issue of racism in news sites and social networks and propose the theory of social representations as a relevant theoretical tool to understand the processes discursive construction of racial identity in this social space. For this divide exploration in the following categories: 1) the Internet as a space for the construction of identity and community formation around ethnic and racial identity; 2) social networks as a place to express racial attitudes; and 3) the social representations as interpretive guiding principles and to study the discursive construction of racial identity.